Analisis Sebaran Suhu Permukaan Laut dan Kaitannya dengan Curah Hujan di Kepulauan Mentawai - Sri Dewi Utami; Mubarak Mubarak; Elizal Elizal (Dinamika Lingkungan Indonesia, 2023)
The Mentawai Islands are directly connected to the Indian Ocean and are located on the equator, making the Mentawai Islands region influenced by the characteristics of the sea surface temperature of the Indian Ocean. This location causes the area to have a hot and humid climate and high rainfall. This study aims to determine the distribution of sea surface temperature, average rainfall, and the relationship between sea surface temperature and rainfall in the Mentawai Islands for 10 years (2012-2021). The method used in this study is a survey method, namely direct observation at the research site. The results of this study indicate that the sea surface temperature in the study area in the wet month (October - March) ranges from 29.05 oC - 29.68 oC. The sea surface temperature in the dry months (April – September) ranges from 30.23 oC – 28.95 oC. The maximum rainfall in the Mentawai Islands Regency occurs in November with an average rainfall of 386 mm while the minimum rainfall occurs in June with an average rainfall of 127 mm. The results of the correlation analysis of sea surface temperature with rainfall in the wet month showed a positive correlation. While in the dry month there is a negative correlation.